Kano Bening Tourism Activities: The Role of TikTok as a Promotional Catalyst at the Turtle Conservation Community, Nipah Beach, Lombok - Putri Sri Handayani (Jurnal Pariwisata Nusantara (JUWITA), 2026)
Purpose:  This study aims to analyze the promotional strategies implemented through TikTok social media in introducing and increasing tourist visits to the Kano Bening tourism attraction at the Turtle Conservation Community (TCC) in Nipah, Lombok Method: This study employed a descriptive qualitative approach. Informants were selected using purposive sampling. The data sources consisted of both primary and secondary data, while data were collected through observation, interviews, and documentation. Result: The findings indicate that TikTok plays a highly significant role in increasing the number of tourist visits to the Kano Bening attraction. Through this interactive promotional medium, information about the Kano Bening tourism experience at TCC Nipah has reached a broader audience, both domestically and internationally. Contribution: This study offers an important contribution by demonstrating a significant shift in tourism marketing and promotional strategies. Marketing through TikTok social media serves as an effective catalyst in influencing tourists' visitation interest and shaping their travel behavior.